Pengaruh Perbedaan Meshsize Gillnet terhadap Hasil Tangkapan Ikan di Perairan Pulau Enggano Bengkulu - Achmad Tedi Mahmudi; Dinda Anastasya Fadhilla (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
This study aims to analyze the effectiveness of gillnet mesh sizes (1 inch and 3 inches) on fish catches in the waters of Enggano Island, Bengkulu. The method used is a quantitative experiment by catching fish using gillnets with mesh sizes of 1 inch and 3 inches for three trips around the waters of Enggano Island. The data collected included the number, length, and weight of fish caught, which were then analyzed using an independent t-test. The results showed that the 1-inch mesh caught more fish than the 3-inch mesh, but the fish caught with the 3-inch mesh were larger in size and weight. Although there were differences in the number and weight of fish caught, the results of statistical tests showed that the differences were not statistically significant, so that both mesh sizes had comparable effectiveness in the context of fishing at the study site. The conclusion of this study shows that the use of a 3-inch mesh is more recommended for getting fish with higher economic value, while a 1-inch mesh is more effective for catching more fish. Further research is recommended to examine other mesh size variations and their impacts on the sustainability of fish resources